2002
DOI: 10.1097/00042737-200207000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after cholecystectomy and after successful lithotripsy for gallbladder stones: a matched-pairs comparison

Abstract: The quality of life after either cholecystectomy or extra-corporeal shock-wave lithotripsy is good overall, but cholecystectomy might be associated with a higher rate of dyspeptic complaints than a gallbladder preserving treatment like extra-corporeal shock-wave lithotripsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The successful rate of the anchor assisted group was high than the guidewire assisted group (92.9% Vs 70%, P=0.07). On the average of 12.25±2.77 (range [8][9][10][11][12][13][14][15][16][17] days after the initial BD drainage procedure, 20 patients received the per-oral cholecystoscopy via the fistula. Fistula broken was found in 2 patients in which the per-oral cholecystoscopy was applied on the ninth day after the EUS-GBD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful rate of the anchor assisted group was high than the guidewire assisted group (92.9% Vs 70%, P=0.07). On the average of 12.25±2.77 (range [8][9][10][11][12][13][14][15][16][17] days after the initial BD drainage procedure, 20 patients received the per-oral cholecystoscopy via the fistula. Fistula broken was found in 2 patients in which the per-oral cholecystoscopy was applied on the ninth day after the EUS-GBD.…”
Section: Resultsmentioning
confidence: 99%
“…This has the potential to become the procedure of choice for gallstones besides LC. Long-term follow-up studies have found that cholecystectomy is associated with an increased incidence of dyspepsia, calculus of the common bile duct, and colon carcinoma 17 . So, LC at young patients could become a potential risk for a life long time.…”
Section: Discussionmentioning
confidence: 99%
“…In their matched-pairs comparison of 36 patients, CE was assoziated with a higher rate of dyspeptic complaints than ESWL (24).…”
Section: Discussionmentioning
confidence: 97%
“…It has the potential to become the procedure of choice for gallstones besides laparoscopic cholecystectomy (LC). Long-term follow-up studies have found that cholecystectomy is associated with an increased incidence of dyspepsia, calculus of the common bile duct, and colon carcinoma 18 . Thus, LC at a young age could become a potential risk for life long.…”
Section: Discussionmentioning
confidence: 99%